Implementasi Kajian Mitologi Film "Gadis Kretek" dalam Pengembangan Keterampilan Literasi Kritis Siswa Sekolah Menengah Atas - Fitria Khoirunnisa; Mahpudoh Mahpudoh; Rina Andriani (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2026)
This study aims to describe the utilization of mythological analysis findings from the Gadis Kretek series as learning material to strengthen critical literacy skills among high school students. This qualitative study employs a descriptive method. The primary data sources consist of scenes, dialogue, and visual symbols from the Gadis Kretek series, while supporting data were obtained through interviews with high school Indonesian language teachers. Data analysis was conducted using an interactive model comprising data reduction, data presentation, and conclusion drawing. The study reveals that the Gadis Kretek series is rich in representations of social myths particularly regarding patriarchal culture and gender stereotypes that are relevant to social realities. Implementation within high school critical literacy instruction involves activities such as viewing the series, identifying denotative and connotative meanings, and analyzing the myths embedded in the audiovisual text. These activities train students to critically decode, interpret, evaluate, and reflect upon media content. The use of film media which is contextual and relatable to students' experiences effectively enhances motivation and active engagement in the critical literacy learning process.